2019
DOI: 10.1002/advs.201901165
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopic Insights of Amphiphilic Peptide against the Oligomer Assembly Process to Treat Huntington's Disease

Abstract: Finding an effective therapeutic regimen is an urgent demand for various neurodegenerative disorders including Huntington's disease (HD). For the difficulties in observing the dynamic aggregation and oligomerization process of mutant Huntingtin (mHtt) in vivo, the evaluation of potential drugs at the molecular protein level is usually restricted. By combing lifetime‐based fluorescence microscopies and biophysical tools, it is showcased that a designed amphiphilic peptide, which targets the mHtt at an early sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Although the amphiphilic JLD1 provided the electrostatic repulsion, the AuNPs offered a steric hindrance to prevent further aggregation. Moreover, the deca-glutamine in JLD1 was able to guide the complex to allure the pathological polyglutamine sequence as also reported He et al in the HD model . In addition to the glutamine tract, the tryptophan-rich sequence was also able to bind mHtt aggregates in the HD Drosophila and mouse model .…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Although the amphiphilic JLD1 provided the electrostatic repulsion, the AuNPs offered a steric hindrance to prevent further aggregation. Moreover, the deca-glutamine in JLD1 was able to guide the complex to allure the pathological polyglutamine sequence as also reported He et al in the HD model . In addition to the glutamine tract, the tryptophan-rich sequence was also able to bind mHtt aggregates in the HD Drosophila and mouse model .…”
Section: Resultssupporting
confidence: 60%
“…We have earlier demonstrated that deca-glutamine-containing peptides interacted with mHtt. , Herein, we incorporated an amphiphilic peptide (JLD1) composed of a polyglutamine-binding sequence (deca-glutamine), a negatively charged sequence (hexa-glutamic acid), and a linker (cysteine–triglycine) on the surface of AuNPs to mitigate mHtt neurotoxicity and disassemble its aggregation (Figure ). The JLD1 was incorporated on the surface of citrate-stabilized AuNPs through gold–sulfur interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation of an mHTT protein was also suppressed by a hybrid peptide, 8R10Q (RRRRRRRRQQQQQQQQQQ; net charge +8.0) designed by He et al (2019) through a principle similar to the bipartite peptide designed for amyloid-beta aggregation by Cheng et al (2017): inclusion of a self-recognition component (a ten-residue stretch of glutamine), conjugated to a polyarginine component to drive charge-based repulsion of bound monomers as well as increase solubility and membrane permeability.…”
Section: Potential Roles For Arginine In Other Neurodegenerative Disease-associated Proteopathiesmentioning
confidence: 99%
“…In behavioral neuroscience, Morris water maze (MWM) and nesting construction (NC) experiments are the most commonly used methods to evaluate learning, memory, and cognitive impairment in AD model animals . Intranasal administration is considered as a feasible route for peptide delivery with a good application prospect. , The bioavailability of the drug through the nasal route is comparable to that through the intravenous route. , The therapeutic agents such as peptides, proteins, viral vectors, nanocarriers, and even stem cells can, through intranasal administration, bypass the BBB and directly enter the central nervous system . Therefore, to determine whether IS@NP/KH could be used as a potential drug for AD, APP/PS1 mice were treated with IS@NP/KH for 3 months through nasal administration, and MWM and NC experiments were performed.…”
Section: Resultsmentioning
confidence: 99%